Comparison on the quality of sterile Aedes aegypti mosquitoes produced by either radiation-based sterile insect technique or Wolbachia-induced incompatible insect technique - Pattamaporn Kittayapong; Suwannapa Ninphanomchai; Parinda Thayanukul; Jiraporn Yongyai; Wanitch Limohpasmanee (PLoS ONE, 2025)
Novel and alternative vector control approaches using a sterile male-based release to suppress Aedes aegypti mosquito vectors have recently been tested in the field in many countries. These approaches included the sterile insect technique (SIT), incompatible insect technique (IIT), and a combination of both techniques. In this study, we conducted a series of experiments to compare the quality between radiation-based and Wolbachia-induced sterile males in terms of flight ability, sterility, mating competitiveness, survival rate, and longevity. Aedes aegypti mosquitoes irradiated at 50 Gy (SIT) and those trans-infected with wAlbB Wolbachia (IIT) were used for quality comparison. Our results showed that irradiated and Wolbachia trans-infected males were not significantly different in flight ability (p > 0.05) and both could induce sterility in wild-type females. In addition, although irradiation at 50 Gy or Wolbachia trans-infection reduced male mating competitiveness, combined irradiation and Wolbachia wAlbB trans-infection increased male competitiveness at the one-to-one ratio. Increasing the number of sterile males released could compensate for reduced competitiveness but it does not make them more competitive. Irradiation did not affect the survival and longevity of irradiated males, but it showed significant negative impacts on females (p < 0.05); while the opposite was observed in the case of Wolbachia infection, i.e., with significant increase in the survival rate of Wolbachia trans-infected males (p < 0.05), but both survival and longevity were reduced in Wolbachia trans-infected females with no significant impacts (p > 0.05). In conclusion, neither irradiation nor Wolbachia trans-infection significantly affected the quality of sterile males except their mating competitiveness; but this could compensate by increasing the number of sterile males released. Sterility could be induced by either 50 Gy irradiation or wAlbB trans-infection. Mating competitiveness results showed that a higher number of sterile males produced by irradiation need to be released in comparison to those produced by Wolbachia trans-infection. Our results should be useful for planning SIT, IIT, or a combination for Ae. aegypti vector control.